Palliative care nursing : quality care to the end of life - Matzo, Marianne; Sherman, Deborah Witt (Springer Pub. Co., 2010)
"This textbook has ... introduced concepts and methods of education which [help] to move palliative nursing forward as an evidenced based practice of whole person care."--Betty Ferrell, PhD, FAAN. Research Scientist (From the Foreword). Palliative care is a philosophy of caregiving that integrates disease modification with supportive, compassionate therapies for patients at the end of life. Palliative care nurses are responsible for alleviating pain and other physical symptoms-along with satisfying the emotional, social, cultural, and spiritual needs of patients who are facing life-